2014
DOI: 10.1007/s12307-014-0145-7
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Infiltration in Tumor Stroma is Related to Tumor Cell Expression of CD163 in Colorectal Cancer

Abstract: The scavenger receptor, CD163, is a macrophagespecific marker. Recent studies have shown that CD163 expression in breast and rectal cancer cells is associated with poor prognosis. This study was conducted to evaluate the relationship between CD163 expression as a macrophage trait in cancer cells, and macrophage infiltration and its clinical significance in colorectal cancer. Immunostaining of CD163 and macrophage infiltration were evaluated in paraffinembedded specimens, earlier analyzed for CD31, D2-40 and S-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 57 publications
(72 reference statements)
3
37
0
Order By: Relevance
“…Apart from CD163, several other TAM markers such as IL-10, iNOS, and VEGF have been used for diagnosis of tumor staging in lung, 38 breast, 39 and colon cancers. 40 The upregulation of CD163, VEGF, and IL-10 and the downregulation of iNOS in LMNCs indicates the presence of M2-like TAMs in our experimental model. Several reports indicate that TAMs perform multiple M2-associated functions including promotion of angiogenesis, matrix remodeling, and suppression of adaptive immunity.…”
Section: Discussionmentioning
confidence: 61%
“…Apart from CD163, several other TAM markers such as IL-10, iNOS, and VEGF have been used for diagnosis of tumor staging in lung, 38 breast, 39 and colon cancers. 40 The upregulation of CD163, VEGF, and IL-10 and the downregulation of iNOS in LMNCs indicates the presence of M2-like TAMs in our experimental model. Several reports indicate that TAMs perform multiple M2-associated functions including promotion of angiogenesis, matrix remodeling, and suppression of adaptive immunity.…”
Section: Discussionmentioning
confidence: 61%
“…Clinical observations have shown that high macrophage infiltration is generally associated with poor prognosis in human cancer, including breast, gastric, prostatic, pancreatic, ovarian, and cervical carcinomas (12)(13)(14)(15)(16). Interestingly, contradictory results have also been reported in several types of human cancers, including colorectal cancer (17)(18)(19)(20)(21)(22). In colorectal cancer, an increased infiltration of TAMs was associated with lymph node metastases and tumor progression (19,21), and M2 macrophage infiltration was associated with poor prognosis in colorectal cancer (20,22).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, contradictory results have also been reported in several types of human cancers, including colorectal cancer (17)(18)(19)(20)(21)(22). In colorectal cancer, an increased infiltration of TAMs was associated with lymph node metastases and tumor progression (19,21), and M2 macrophage infiltration was associated with poor prognosis in colorectal cancer (20,22). However, increased macrophage infiltration was also reported to correlate with improved survival in colorectal cancer (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of CD163 + macrophages was suggested to have a stronger association with less favorable clinicopathological features than CD68 + macrophages (Medrek, Ponten, Jirstrom, & Leandersson, 2012). Numerous studies demonstrate that elevated CD163 expression correlates with advanced cancer stages, unfavorable prognosis, early distant recurrence, and reduced patient survival in various types of cancer, which include melanoma (Jensen et al, 2009), meningioma (Kanno et al, 2013), breast cancer (Mansfield, Heikkila, von Smitten, Vakkila, & Leidenius, 2012; Shabo, Stal, Olsson, Dore, & Svanvik, 2008; Tiainen et al, 2014), colorectal cancer (Edin et al, 2012; Shabo, Olsson, Elkarim, Sun, & Svanvik, 2014), oral squamous cell carcinoma (He, Bao, et al, 2014; Wang et al, 2014), ovarian carcinoma (Reinartz et al, 2014), HCC (Kong et al, 2013), angiosarcoma (Fujimura et al, 2013), glioma (Komohara et al, 2008), and gastrointestinal stromal tumors (van Dongen et al, 2010), and hematopoietic malignancies, such as T cell leukemia/lymphoma (Komohara et al, 2013), acute myeloid leukemia (Garcia, Gardner, & Reichard, 2008), and classical Hodgkin lymphoma (Klein et al, 2014; Koh, Park, Yoon, Suh, & Huh, 2014). A recent study showed that relapse of head and neck cancer after chemoradiotherapy also correlated with CD163 + macrophages in primary tumor and CD11b + myeloid cells in recurrences (Balermpas et al, 2014).…”
Section: Scavenger Receptors In Cancer Immunobiologymentioning
confidence: 99%